Sport and active recreation injuries in Australia: evidence from emergency department presentations. Issue 3 (September 1998) - Finch, C; Valuri, G; Ozanne-Smith, J
Abstract : OBJECTIVE: Despite the rise in specialist clinical services for the management of sports and active recreation injury, many patients attend hospital emergency departments for treatment. The purpose of this study was to describe sports injury cases presented to selected hospital emergency departments around Australia for the period 1989-1993. METHODS: Routinely collected emergency department injury presentation data from the Australian National Injury Surveillance Unit were examined. Data on 98, 040 sports and active recreation emergency department presentations were analysed. Sports and active recreation activities were ranked according to frequency of presentation. Relative proportions of injury type and body region injured were determined. Data are presented separately for children (<15 years of age) and adults (>15 years of age). RESULTS: Among the 10 activities that most commonly led to a sports or active recreation injury presentation for all ages were cycling, Australian football, basketball, soccer, cricket, netball, and rugby. For children, injuries were also commonly associated with roller skating/blading, skateboarding, and trampolining. Hockey, martial arts, and dancing injuries were frequent in adults. Most sporting injuries occurred during organised competition or practice whereas the active recreation injuries occurred in a variety of settings. Fractures, strains, and sprains, particularly to the lower and upper extremities, were common types of injury. CONCLUSION: The rich, but nevertheless limited, information available about sports and active recreation injuries from data collected in emergency departments indicates that these activities are a common context for injury at the community level in Australia.